Electrospun zinc-manganese bimetallic oxide carbon nanofibers as freestanding supercapacitor electrodes - Joshi, Bhavana; Samuel, Edmund; Kim, Yongil; Kim, Taegun; El-Newehy, Mohamed; Aldalbahi, Ali; Yoon, Sam S. (International Journal of Energy Research, 2022)
Flexible, lightweight, and freestanding zinc-manganese oxide carbon nanofibers are promising materials for the fabrication of portable electronic devices. Composite nanofibers were synthesized using terephthalic acid and sodium dodecyl sulfate. Terephthalic acid improves the flexibility of the composite fibers and facilitates the diffusion of electrolytic ions. Meanwhile, sodium dodecyl sulfate aids to elevate the metal (zinc) oxide particles to the surface of the nanofibers during annealing. The texturing of the carbon nanofiber surface with ZnO enhances the electrochemical activity of the composite fibers. Parametric studies were conducted by varying the weight ratio of zinc and manganese acetates from zero to unity. The optimal case with a ratio of 0.75 produces specific capacitances of 1080 and 817 F center dot g(-1) at current densities of 1 and 10 A center dot g(-1), respectively, with a wide potential window of 1.6 V, indicating outstanding energy storage capabilities. The capacitance retention was 92% after 10 000 galvanostatic charge-discharge cycles. The bending angle test confirmed the mechanical durability of the freestanding carbon nanofiber electrodes, and the corresponding change in the cyclic voltammetry curve was negligible.
Keywords: electrospinning; freestanding electrode; high-energy-density; supercapacitor; ZnMn2O4